The Effect of Cognitive Behavioral Therapy through Recitation and Prayer on Reducing Smartphone Addiction In College Students - Salsabila Nur Kamilah; Ahmad Arfandi; Muhammad Iqbal Alhadii (CV. Doki Course and Training, 2025)
The purpose of the research we conducted was to determine the effect of Cognitive behavioral therapy through mngengaji and prayer on reducing smartphone addiction in students of the Faculty of Psychology, Raden Fatah State Islamic University Palembang. The research we conducted used the One-Group Pretest-Posttest Design pre-experiment design method. The results of the research and conclusions are that there is a very significant difference in smartphone addiction in students in the dimension of Disrupting Daily Life decreased from the pretest percentage score of 80% to the posttest percentage score of 41% with an N-Gain value of 0.38. Then the Positive Anticipation dimension decreased from the pretest percentage score of 72% to the posttest percentage score of 58% with an N-Gain value of 1.00. Then the Withdrawal dimension decreased from the pretest percentage score of 54% to the posttest percentage score of 46% with an N-Gain value of 0.09. Then the Cyberspace-Oriented Relationship dimension decreased from the pretest percentage score of 63% to the posttest percentage score of 50% with an N-Gain value of 0.22. Then the Excessive Use dimension decreased from the pretest percentage score of 71% to the posttest percentage score of 46% with an N-Gain value of 0.41. Finally, the Tolerance dimension decreased from the pretest percentage score of 72% to the posttest percentage score of 47% with an N-Gain value of 0.06.